2011
DOI: 10.1111/j.1360-0443.2011.03443.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among a cohort of drug users after their release from prison: an evaluation of the effectiveness of a harm reduction program in Taiwan

Abstract: In ex-prisoners in Taiwan with a history of opiate injecting, enrollment and continued participation in methadone maintenance treatment is associated with substantially lower mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 21 publications
5
51
0
Order By: Relevance
“…Prior studies found that this IDU subgroup more often participated in injecting behaviors associated with HIV infection [25,26]. In addition, a cohort study in Taiwan showed that more than 40% of IDUs began using drugs again within 1.5 years after release from a correctional setting [27]. To better control the HIV epidemic among IDUs, incarcerated IDUs should receive education about HIV infection and, once released, should be strongly encouraged to refrain from drug use (eg, through harm reduction programs) [28].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies found that this IDU subgroup more often participated in injecting behaviors associated with HIV infection [25,26]. In addition, a cohort study in Taiwan showed that more than 40% of IDUs began using drugs again within 1.5 years after release from a correctional setting [27]. To better control the HIV epidemic among IDUs, incarcerated IDUs should receive education about HIV infection and, once released, should be strongly encouraged to refrain from drug use (eg, through harm reduction programs) [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented that over 40% of people who inject drugs in Russia have been previously incarcerated (Dolan et al, 2007) and despite an incarceration rate of over 500 per 100,000 (Walmsley, 2011), the Russian prison system suffers from a lack of effective linkage to care services for prisoners being released. This is especially evident regarding opioid substitution therapy, which remains illegal in Russia despite compelling international evidence that it can reduce the incidence of reincarceration (Larney et al, 2012), death (Dolan et al, 2005; Huang et al, 2011; Kinlock et al, 2009) and delay relapse (Gonzalez et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…The Taiwanese program includes methadone maintenance and needle exchange services throughout the country (Yang, Yang, Shen, & Kuo, 2008). The initiation of this countrywide harm reduction program has been linked to a dramatic decrease in HIV infections and mortality among drug users (Huang et al, 2011). • Although Vietnam has very low coverage, there are plans to increase methadone maintenance availability; yet with limited resources, Vietnam will need additional funds to provide a reasonable number of methadone maintenance slots as well as address police harassment of people who use drugs (Jardine, Crofts, Monaghan, & Morrow, 2012).…”
Section: Harm Reduction In Asiamentioning
confidence: 99%